Carcinoma of the lung in the absence of asbestosis: The value of lung fiber burden analysis. (3rd May 2016) - Roggli, Victor L.; Sporn, Thomas A.
ABSTRACT: Asbestos is universally recognized as a carcinogen for the lower respiratory tract. However, asbestos is a contributory factor in a small fraction of lung cancers, the vast majority of which are related to cigarette smoking. The challenge for the pathologist is to determine when a lung cancer may be attributed to past asbestos exposure. The finding of asbestosis either clinically or pathologically is a useful marker for such a determination. However, in the absence of asbestosis, it has been suggested that a fiber burden as determined by analytical electron microscopy within the range of asbestosis is sufficient for determination of a causal contribution. We report here an example of a case of lung cancer in which fiber burden studies showed an asbestos concentration within the range of asbestosis as determined by scanning electron microscopy (SEM).